Fuzzy modeling on wheat productivity under different doses of sludge and sewage effluent - Putti, Fernando F. [UNESP]; Kummer, Ana C.B.; Filho, Helio Grassi [UNESP]; Filho, Luís R.A. Gabriel [UNESP]; Cremasco, Camila P. [UNESP] (FapUNIFESP (SciELO), 2017)
This study aimed to evaluate the effects of fertilization with composted sewage sludge and irrigation with drinking water (DW) and fertigation with wastewater (WW) in wheat crop using fuzzy rule-based system. The experiment was conducted in the Department of Soil and Environmental Resources, of FCA, UNESP - Botucatu, with factorial 6 × 2, which were applied 6 doses of sewage sludge (0, 50, 100, 150, 200 and 250% of nitrogen recommendation) and two types of effluents (treated water and sewage). In the developing of the system based in fuzzy rules, it was used the Mamdani inference method, where the input variables were sewage sludge doses and water types and the output variables used were the number of tillers, length and number spike per plant; number of spikelet per plant, grain mass per spike and dry mass of the aerial parts. It can be seen that the sewage sludge and the effluent contributed to the higher increase of production, and at 150% sludge dose occurred higher production.
Keywords: Fuzzy system; Mamdani; Nitrogen; Sustainability